The Development of Pathogenicity of Avian Influenza Virus Isolated from Indonesia - Michael Haryadi Wibowo; Agus Eko Srihanto; Khrisdiana Putri; Widya Asmara; Charles Rangga Tabbu (Universitas Gadjah Mada, 2013)
Highly pathogenic avian infl uenza outbreak in Indonesia has been reported in various poultry due toH5N1 subtype. The presence of multiple basic amino acids within the cleavage site of HA glycoprotein hasbeen identifi ed to be associated with the pathogenicity of avian infl uenza virus. The study was retrospectivestudy which was designed to characterize the cleavage site and fusion site region of haemagglutinin gene ofAIV isolated from various poultry in 2003 to 2013. Isolation, Identifi cation and propagation were carried outto collect viral stock. For virus detection, reverse transcriptase PCR (RT-PCR) method on H5 and N1 genefragment was performed. All of RT-PCR HA gene positive products were sequenced for further nucleotideanalysis and to determine the nucleotide composition at the targeted fragment. The results are all AIV isolateswere identifi ed as H5N1 subtype. The sequence analyses revealed some motives of basic amino acid motivethat were classifi ed as highly pathogenic avian infl uenza virus. Further analyses on fusion domain of all AIVisolated during the period 2003 to 2013 showed conserved amino acid. Keywords: avian infl uenza, haemagglutinin, cleavage site, basic amino acid, fusion site